EXPORTING PROBLEMS OF MALAYSIAN SMES : A RECENT SURVEY - Mahajar, Abdul Jumaat; Hashim, Mohd Khairuddin (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
The notion that exporting provides firms with both a growth opportunity and a major challenge has produced an extensive stream of studies. While a good number of empirical studies have concentrated on the exporting problems of firms in western and developed business societies, limited research has examined problems faced by Malaysian small and medium-sized enterprises (SMEs). This study attempts to address this issue. The findings of the study suggest that Malaysian SMEs faced exporting problems as espoused in the literature